Clinical application of 3D slicer reconstruction and 3D printing localization combined with neuroendoscopy technology in VPS surgery - Long Zhou; Pan Lei; Ping Song; Zhiyang Li; Huikai Zhang; Hangyu Wei; Lun Gao; Qiuwei Hua; Hui Ye; Qianxue Chen; Silei Zhang; Qiang Cai (Scientific Reports)
Abstract To explore techniques, advantages and disadvantages of 3D Slicer reconstruction and 3D printing localization technology combined with transcranial neuroendoscopy in ventriculoperitoneal shunt surgery. Retrospective analysis of clinical data of patients with hydrocephalus treated by ventriculoperitoneal shunt surgery using 3D Slicer reconstruction and 3D printing positioning technology combined with transcranial neuroendoscopy in our hospital from October 2021 to March 2023. A total of 33 patients with complete data were collected, including 19 males and 14 females, aged 10–81 years. Pre operative use of 3D Slicer reconstruction and 3D printing localization, and intraoperative use of neuroendoscopy assisted catheterization to complete ventriculoperitoneal shunt surgery. The drainage tube position was confirmed by brain CT and 3D Slicer reconstruction after operation, of which 30 cases were located in the frontal horn or center of the ipsilateral lateral ventricle, and 3 cases were located in the frontal horn or center of the contralateral lateral ventricle. All patients were successfully catheterized and well positioned. According to the unique ventricular system characteristics of each hydrocephalus patient, the 3D Slicer reconstruction technology was used to determine the individualized puncture point and direction, measure the puncture depth, accurately locate the puncture through the 3D printing guide plate, and accurately send the tip of the ventricular catheter into the frontal or central part of the lateral ventricle with the assistance of neuroendoscopic visualization, which improved the success rate of the operation and reduced the risk of tube blockage. At the same time, our team has newly developed a puncture point (“Cai’s point”), which has a puncture path in a non-vascular area and can reduce the risk of puncture bleeding. However, further prospective clinical research is needed to determine its routine location.